INHIBITING STEROL BIOSYNTHESIS WITH RING C OXYGENATED CHOLESTEROL DERIVATIVES: A CHEMICAL SYNTHESIS APPROACH - Tanoto, Sarah L.; Williams, Daniel K. (Global Journal of Chemistry, Biology and Physics (GJCBP), 2023)
Oxysterols, defined as sterols with an additional oxygen function, have emerged as compounds of significant interest due to their diverse and multifaceted biological properties. This review explores the various aspects of oxysterols, including their cytotoxicity, atherogenicity, carcinogenicity, mutagenicity, hypocholesterolemia, and effects on specific enzymes. These compounds are not only found widely distributed in nature but are also present in animal tissues and food items. Furthermore, oxysterols have been isolated from natural drugs employed in traditional medicine for cancer treatment. In this review, we delve into the biological implications and sources of oxysterols, shedding light on their potential impact on human health and offering insights into their relevance in both the natural world and therapeutic practices